Deskripsi Pola Asuh Orang Tua Kelompok A di TK Negeri Pembina - Rapi Us. Djuko; Icam Sutisna; Ayu Sulistiami Tawaa (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
The purpose of this study was to determine the parenting style of children aged 4-5 years at the TK Negeri Pembina, West Wonggarasi Village, Lemito District, Pohuwato Regency. A qualitative approach was used as a research method involving 15 parents. Based on the results of interviews and observations, it was found that several parenting styles were democratic parenting, authoritarian parenting, and permissive parenting. The majority of parents tend to choose permissive parenting because they are busy so they cannot give much time to guide and listen to their children's opinions.